ANALISIS WACANA KRITIS TERHADAP PEMBERITAAN KEBANGKITAN PKI PADA ARTIKEL - ARTIKEL DI MEDIA DARING “SEWORD.COM” - Fitri Detya Wulansari; Nunik Karina Widiastuti; Reka Yuda Mahardika (IKIP Siliwangi, 2018)
Social media is a communication and information which becomes the prima donna millennial generation now in the era of. All the circles have been able to access information in social media easily and quickly, cannot be separated from social status, the age of, or their education. Only by determining to gawai and access the internet, all of the required information can easily are represented in tabular form. Easier the information obtained, sometimes, the information has not yet been filtered out well. As the issue of which recently are evolve in the community that is the issue of the resurrection of PKI which has reported, both in the mass media and electronic media. The purpose of this research analytics critically against diction and phrases used by the media to represent the resurrection PKI in online media seword.com site. The kind of research for this article is qualitative descriptive by using the method and results of the research is described as it were. Through the analysis of some article contained in seword.com site, were found damaged diction and sentence was alleged to contain a tendentious the group or certain parties. Hence by discourse critical analysis to open a new knowledge to public readers to be wise in the read a message that flourished in the media.